2015
DOI: 10.1002/2014je004756
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for different episodes of aeolian construction and a new type of wind streak in the 2016 ExoMars landing ellipse in Meridiani Planum, Mars

Abstract: We present evidence for a complex, multigenerational bed form pattern and a new type of wind streak (the ripple streak) in the landing site ellipse of the 2016 ExoMars Entry descent and landing Demonstrator Module (EDM) in Meridiani Planum (Mars). We identified three main groups of bright-toned bed forms. Population 3, represented by NE-SW trending bed forms located inside craters, was emplaced by winds coming from the NW or the SE. Population 2, emplaced by strong easterlies, formed by intracrater transverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…The meter-scale bedforms on Herschel are morphologically different from Martian intracrater TARs, but present some overlap with the plain ripples mapped by Silvestro et al (2015a) in Meridiani Planum. Terrestrial aeolian megaripples also present similar H-index values for lower wavelengths, although the reduce number of measurements we show are probably not representative of the variance that those bedforms present in our planet.…”
Section: Bedform H-index Comparisonmentioning
confidence: 88%
“…The meter-scale bedforms on Herschel are morphologically different from Martian intracrater TARs, but present some overlap with the plain ripples mapped by Silvestro et al (2015a) in Meridiani Planum. Terrestrial aeolian megaripples also present similar H-index values for lower wavelengths, although the reduce number of measurements we show are probably not representative of the variance that those bedforms present in our planet.…”
Section: Bedform H-index Comparisonmentioning
confidence: 88%
“…Multiple studies have now revealed present-day movement of sand by the wind and migration of bedforms (dunes and ripples collectively) in some environments in the current Martian climate and~6-mbar atmosphere (e.g., Banks et al, 2015;Banks et al, 2017;Bourke et al, 2008;Bridges et al, 2010Bridges et al, , 2012Bridges et al, , 2013Chojnacki et al, 2011Chojnacki et al, , 2014Chojnacki et al, , 2015Chojnacki et al, , 2017Chojnacki et al, , 2018aChojnacki et al, , 2018bFenton, 2006;Silvestro et al, 2010Silvestro et al, , 2011Silvestro et al, , 2013Silvestro et al, , 2016Sullivan et al, 2008). Dune field and sand sheet formation, activity, and stabilization, on both Earth and Mars, are driven by factors such as sediment availability and wind transport capacity, potentially initiated by changes in climatic conditions (e.g., Ayoub et al, 2014;Fenton et al, 2015Fenton et al, , 2018Kocurek, 1998;Kocurek et al, 2007;Kocurek & Lancaster, 1999;Runyon, Bridges, Ayoub, et al, 2017;Silvestro et al, 2015).…”
mentioning
confidence: 99%
“…The plains ripples are aligned nearly north‐south (N‐S), at 002.5° (Fenton et al, ; Sullivan et al, ). Exposed crossbedding (Arvidson et al, ; Sullivan et al, ) and the presence of westward‐pointing ripple streaks (Fenton et al, ; Silvestro et al, ) indicate that the plains ripples are transverse bedforms built by unimodal easterly (~092.5°) winds. The age of the ripples is not known, but they were in place prior to an impact event at ~200 ka (Golombek et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Meridiani Planum on Mars has been the site of Mars Exploration Rover Opportunity 's traverse (centered at ~354.5°E, 2.1°S) over tens of kilometers of coarse‐grained ripples called “plains ripples” (e.g., Arvidson et al, ; Squyres et al, ). The plains ripples (see Figure a) typically have a wavelength of 2–4 m, crest lengths ranging from a few to several tens of meters, and heights of ~0.1–1 m (Golombek et al, ; Silvestro et al, ; Zimbelman et al, ). Similar to coarse‐grained ripples on Earth (also known as megaripples), the Meridiani plains ripples are composed of grains with a bimodal size distribution, with a monolayer of 1–2 mm rounded fragments of hematite concretions armoring an interior dominated by grains <250 μm in diameter (Sullivan et al, ; Weitz et al, ).…”
Section: Introductionmentioning
confidence: 99%